Assessment of the Impact of Herbal Drugs Used in Neurodegenerative Disorders: A Preclinical Review - Sharma, Maandvi; Awasthi, Himani; Srivastava, Dipti; Fatima, Zeeshan; Srivastava, Vivek (Current Traditional Medicine, 2022)
The use of herbal drugs may offer great potential opportunities in preventing and controlling neurodegenerative disorders, such as Alzheimer’s disease, Parkinson’s disease and Huntington’s disease. Herbal drugs contain multiple pharmacologically active constituents. The relative amounts and nature of these constituents vary due to diverse factors, such as plant source and plant parts, extraction methods, local environmental conditions, storage conditions, adulterations, and accidental or intentional contamination. After administration, they are put through the processes of absorption, distribution, metabolism, and excretion of the same as modern medicines. When handled by the body, they can show a combined effect and interact with modern drugs due to various factors, including similar transport protein interaction, metabolizing cytochrome P450 enzyme, and different transporter mechanisms. Herbal medicine can either induce or inhibit CYP450 enzymes. When herbs are combined with the drugs, either they mimic or oppose the effect of drugs. Many studies worldwide indicate the favorable properties of plant extracts or their bioactive compounds against neurodegenerative disorders, but several clinical concerns have appeared regarding the use of these combinations, which could be due to lack of evidence and scientific support for their effectiveness and safety of the patient.
Keywords: Parkinson’s